Pembuatan biochar dari sekam padi sebagai sumber pengetahuan baru bagi mahasiswa di Greenhouse Universitas Sulawesi Barat - Ismail, Muhammad; Kornelius, Kornelius; Taqwa, Taqwa; Rosita, Rosita; Nurawalia, Gina (Jurnal Tarreang: Tren Pengabdian Masyarakat Agrokompleks, 2024)
The objectives of this community service activity were conducted through socialization and training, including (1) enhancing the utilization of agricultural waste such as rice husks into biochar and (2) training on biochar production and its application on land. These activities used the Service Learning (SL) method and involved the community, especially students, as the primary target. The activities were conducted in the Greenhouse by all of the Agroecotechnology Study Program students in the class of 2022 at Universitas Sulawesi Barat. In this community service, students who had studied biochar production explained the process and benefits of biochar based on the materials they learned during lectures. The participants were very enthusiastic about these activities, proved by their statements that they understood the material presented by the speakers.